Penerapan Restorative Justice Dalam Penyelesaian Tindak Pidana Kecelakaan Lalu Lintas Di Polrestabes Makassar - S., M. Wahyudin (Al-Hikmah, 2019)
The research was conducted and aimed at: 1) To find out the application of the Restorative Justice in the resolution of traffic accident cases in the Makassar Porestabes; 2) To find out and analyze what factors are the inhibitors of the Satlantas Polrestabes Makassar Investigator in implementing the Restorative Justice traffic accident. This type of research is empirical legal research, namely legal research that examines the implementation or implementation of positive legal provisions (legislation) factually on any particular legal event that occurs in society. The legal material used consists of primary legal data and secondary legal data. Techniques for collecting legal data are collected through literature studies and field studies. Then the technique for analyzing with qualitative analysis techniques by sorting and selecting, classifying, and connecting the realities that occur in the field with the problems studied, so as to provide a clear picture of what happened in the field so that it comes to a conclusion. The results of the study show that: 1) The application of Restorative Justice to traffic accidents at the Makassar Polrestabes has been running optimally, it can be seen from the many cases of traffic accidents handled can be resolved peacefully using the restorative justice approach; 2) The inhibiting factor in the application of restorative justice at the Makassar Polrestabes is its legal factor that has not explicitly re gulated the settlement of traffic accidents, the investigator's lack of resources when compared with the number of cases handled. Community factors that sometimes do not want peace or requests from the victims or the families of victims who ask for compensation that is too large so the perpetrators cannot.